Role of Exchange Interactions in the Magnetic Response and Intermolecular Recognition of Chiral Molecules - Dianat, Arezoo; Gutierrez, Rafael; Alpern, Hen; Mujica, Vladimiro; Ziv, Amir; Yochelis, Shira; Millo, Oded; Paltiel, Yossi; Cuniberti, Gianaurelio (Giovanni) (Nano Letters, 2020)
The physical origin of the so-called chirality-induced spin selectivity (CISS) effect has puzzled experimental and theoretical researchers over the past few years. Early experiments were interpreted in terms of unconventional spin-orbit interactions mediated by the helical geometry. However, more recent experimental studies have clearly revealed that electronic exchange interactions also play a key role in the magnetic response of chiral molecules in singlet states. In this investigation, we use spin-polarized closed-shell density functional theory calculations to address the influence of exchange contributions to the interaction between helical molecules as well as of helical molecules with magnetized substrates. We show that exchange effects result in differences in the interaction properties with magnetized surfaces, shedding light into the possible origin of two recent important experimental results: enantiomer separation and magnetic exchange force microscopy with AFM tips functionalized with helical peptides.
CRIS-Team Scopus Importer:2022-04-14
Keywords: broken symmetry; CISS effect; Density-Functional Theory; Exchange Effects; Helical Molecules